2004
DOI: 10.1111/j.1365-2648.2004.03079.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ use of online clinical evidence

Abstract: Use of online evidence was associated with nursing role, and with managerial and organizational support. Diffusion of innovation theory can help to explain some of the patterns observed. The use and impact of online evidence should be interpreted in the context of nursing practice and culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 36 publications
5
56
0
3
Order By: Relevance
“…Our findings, fitting with previous studies of nurses' use of electronic information tools [6,7], suggest that nurses will largely use electronic information tools such as the NeLH to access information for CPD courses. Previous studies in acute settings point to how the temporal rhythms of work allow clinicians to anticipate what information they will need, enabling them to access it prior to the point at which it is needed [22].…”
Section: Nurses' Use Of Electronic Information Sourcessupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings, fitting with previous studies of nurses' use of electronic information tools [6,7], suggest that nurses will largely use electronic information tools such as the NeLH to access information for CPD courses. Previous studies in acute settings point to how the temporal rhythms of work allow clinicians to anticipate what information they will need, enabling them to access it prior to the point at which it is needed [22].…”
Section: Nurses' Use Of Electronic Information Sourcessupporting
confidence: 88%
“…Use of online resources tends to be in relation to continuing professional development (CPD) courses [6,7]. A survey of use of NHSnet in general practice conducted in 2001, which included 325 practice nurses/nurse practitioners, found that 64% of practice nurses had easy access to the internet, but only 37% had heard of NeLH [8].…”
mentioning
confidence: 99%
“…The intensity, timing, availability and quality of training has been found to reduce end-user resistance and improve end-users' outlook on EHR systems, in several extant studies [89,64,90,91]. However, Bru-HIMS end-users were given training in functions that were not needed in the dental department, and they struggled to get appropriate technical training and support from the vendor -a problem that appears to be frequent with HIS implementation despite its impact in potentially improving the experience of clinicians [92,46,93].…”
Section: Yh Sidek Jt Martins I N T E R N a T Io N A L J O U R N mentioning
confidence: 99%
“…It implies a requirement for nursing students to develop the kinds of information literacy skills needed for effectively researching the evidence base (Willmer, 2005:474). This is especially significant as Gosling et al (2004) discovered that many nurses still did not feel that exploring, and subsequently using, online, clinical evidence was a legitimate part of their role. Clearly, there is potential for developing nursing students' ICT skills through blended delivery models, thereby incorporating them within the more authentic and meaningful framework of the wider nursing curriculum (Kenny, 2002).…”
Section: Ict Integrationmentioning
confidence: 99%